DISPUTE SETTLEMENT ANALYSIS OF THE INDONESIAN SOLIDARITY PARTY STUDY OF THE ELECTION SUPERVISORY AGENCY'S DECISION, BANDAR LAMPUNG CITY NUMBER: 01.PS.REG.BWSL.BDL.08.01.VII.2018. - Erika Norliza’Aini; Erina Pane; Lintje Anna Marpaung (Universitas Lampung, 2019)
Election Oversight Body or Bawaslu is demanded to be more active in following up on all findings and reports of alleged violations of the election both in the case of election disputes from one stage to another so that elections can run smoothly, safely and in an orderly manner, which Bawaslu also has the authority to adjudicate the election dispute process so that Bawaslu has the power to make a decision on the election dispute process as well as in resolving disputes between the General Election Commission or KPU and the Indonesian Solidarity Party or PSI. The problem to be discussed in this study is how the process of electoral dispute resolution between the Indonesian Solidarity Party and the Bandar Lampung KPU in the Bandar Lampung City Bawaslu is? And what is the authority of Bawaslu in the process of resolving disputes between PSI and KPU? The research results showed that the Dispute Resolution Mechanism between the Bandar Lampung City KPU and PSI on the Bawaslu Decision Number: 01.PS.REG.BWSL.BDL.08.01.VIII.2018 was by the 2017 election law Article 103 letter c and Agency Regulations Election Oversight Number 18 of 2017. The authority of the Bandar Lampung City Bawaslu in deciding an election dispute case is in accordance with the 1945 Constitution and applicable regulations so that justice and human rights can be upheld relatively, and the equality of gender that already exists in the provisions of the legislation can be carried out correctly and adequately so that the election stages can run smoothly. It is in line with the tagline of the Election Oversight Body